THE CORRELATION BETWEEN STUDENTS’ SELF-ESTEEM AND THEIR ENGLISH SPEAKING PERFORMANCE AT SMA NEGERI 1 MORONGE - Sumendap, Angely Christia; Liando, Nihta V. F.; Wongkar, Yapi (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The aim of this study is to investigate the potential relationship between students' speaking performance and their self-esteem. The study was carried out at SMA Negeri 1 Moronge. Students in grades 10, 11, and 12 comprised the research subjects, with seven students from each class, for a total of 21 students. Quantitative data are the kind that are used. A speaking exam and a self-esteem questionnaire with the Rosenberg Self-Esteem Scale were used to collect the data, which were then manually correlated using the Pearson Product-Moment method for analysis. The correlation coefficient, or r, between students' speaking learning achievement and their self-esteem is 0.745 according to the Pearson Product Moment Correlation Coefficient. The study's findings indicate that speaking skills at SMA Negeri 1 Moronge and students' self-esteem are highly correlated. It was shown that there was a strong correlation between students' speaking skills in English classes and their level of self-esteem